Neurocognitive mechanisms of emotional interference in native and foreign languages: evidence from proficient bilinguals - Del Maschio, Nicola; Sulpizio, Simone; Bellini, Camilla; Del Mauro, Gianpaolo; Giannachi, Matteo; Buga, Duygu; Fedeli, Davide; Perani, Daniela; Abutalebi, Jubin (Frontiers in Behavioral Neuroscience, 2024)
Currently available data show mixed results as to whether the processing of emotional information has the same characteristics in the native (L1) as in the second language (L2) of bilinguals. We conducted an fMRI experiment to shed light on the neurocognitive mechanisms underlying bilinguals' emotional processing in L1 and L2 during an emotional interference task (i.e., the Emotional Stroop Task -EST). Our sample comprised proficient Italian-English bilinguals who learned their L2 during childhood mainly in instructional rather than immersive contexts. In spite of no detectable behavioural effects, we found stronger brain activations for L1 versus L2 emotional words in sectors of the posteromedial cortex involved in attention modulation, episodic memory, and affective processing. While fMRI findings are consistent with the hypothesis of a stronger emotional resonance when processing words in a native language, our overall pattern of results points to the different sensitivity of behavioural and hemodynamic responses to emotional information in the two languages of bilingual speakers.